Manajemen Komunikasi Pada Pondok Pesantren - Laily Alfi Zaitun Nisa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Pondok Pesantren, Islamic boarding schools, play a crucial role in shaping the character of young generations. Effective communication management is essential to ensure the smooth execution of various educational, religious, and social activities. This study aims to analyze the concepts, objectives, functions, strategies, and influencing factors of communication management in Pondok Pesantren. The research method used is library research, which involves reviewing relevant literature. The findings indicate that communication management in pesantren encompasses planning, organizing, executing, and supervising communication processes to ensure effective dissemination of religious and educational messages. The primary goals of communication management are to achieve understanding, build acceptance, and motivate action. The functions of communication management include planning, organizing, executing, and controlling. Communication strategies are divided into internal strategies, such as dialogic communication, sharing, counseling, and interviews between caregivers and students, and external strategies, such as interpersonal dialogue, religious lectures, visits, provision of business capital, and zakat to the community. Factors influencing communication management include interaction, motivation, ethics, internal communication within the pesantren, and religious relationships within the community. With effective communication management, Pondok Pesantren can enhance the quality of education and character building for students and provide positive impacts on the community.